Endovascular Thrombectomy: Tirofiban Increases Bleeding Risk in Acute Stroke Patients. Issue 11 (November 2018) - Wu, Yuefei; Yin, Congguo; Yang, Jianhong; Jiang, Lin; Parsons, Mark W.; Lin, Longting
Abstract : Background and Purpose—: This study aimed to explore safety of tirofiban in endovascular treatment of acute ischemic stroke. Methods—: Two hundred eighteen ischemic stroke patients receiving endovascular thrombectomy were prospectively recruited, with 94 treated with intra-arterial tirofiban and 124 were not. The 2 groups were compared in terms of symptomatic intracranial hemorrhage (ICH) and fatal ICH rate by the χ 2 test and logistic regression. Results—: Patients treated with tirofiban compared with those without tirofiban had significantly higher rate of symptomatic ICH (14.6% versus 5.7%; P =0.027) and fatal ICH (8.8% versus 1.6%; P =0.014). Tirofiban-treated patients had increased odds of symptomatic ICH by 2.9-fold (95% CI, 1.1–7.5), and odds of fatal ICH increased by 5.9-fold (95% CI, 1.2–28.4). Conclusions—: Tirofiban treatment increases risk of major ICH after endovascular thrombectomy for acute ischemic stroke in this nonrandomized study. Abstract : Supplemental Digital Content is available in the text.